A Secure NFC-Based Mobile Printing Service Using Recognition Robot - Eunmi Lee; Hongjin Yeh; Hyo-Sik Yang; Seungbin Moon; Okkyung Choi (International Journal of Distributed Sensor Networks)
With the rapid growth of internet technologies, there have been many recent innovations in printing methods and mobile printing service has become important part of our daily life. In this paper, we design and implement a secure mobile printing service using NFC tag to protect our personal information from the technical vulnerability and physical accident such as a robbery. To protect the personal information, the user has to scan the NFC information at the NFC reader using recognition robot to confirm the authentication. In addition, we propose a secure NFC-based authentication protocol that provides printer authorization method and document access control in accordance with user's authority. Lastly, to prove validity and efficiency of the proposed system, the experimental test was confirmed and provided the results.